Pemberian Terapi Musik terhadap Pengetahuan Kecemasan Ibu Hamil di Desa Bangun Rejo Kecamatan Tanjung Morawa Provinsi Sumatera Utara Tahun 2025 - Zulkarnain Batubara; Rosmega Rosmega; Imran Saputra Surbakti; Lisdayanti Simanjuntak; Riezky Laksamana; Salju Salju; Siti Nurcahaya Br Agian (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
At the Sumatera Province Tanjung Morawa District exactly at Bangun Rejo Vilage, The high prevalence of anxiety among pregnant women in this region is influenced by high salt consumption exceeding recommendations, irregular eating patterns due to the background of the majority of the population as fishermen, and low compliance with pharmacological therapy due to concerns about side effects on the fetus. As a mitigation effort, non-pharmacological interventions were carried out in the form of music therapy and education about healthy eating patterns. This Community Service Program (PKM) aims to increase knowledge and reduce anxiety levels in pregnant women through lecture methods and the application of music therapy. The implementation method includes health education and structured music therapy. The results of the intervention showed an 89% increase in knowledge of pregnant women regarding diet, as well as a decrease in anxiety levels with an average value (mean) of 1.17 in the third to fourth week of therapy.